论王畿的 “三教合一” 观 = Wang Ji's thought and "Unity of the Three Teachings" - 陈碧琪 Tan, BiQi (Nanyang Technological University, 2023)
王畿“三教宗盟”的称号，是通过继承王阳明的“三教一道”和“三教归儒”的思想。王畿不仅能够对因朱熹而引发的异端之说给出一个回答，还对儒释道的“毫厘之辨”解释自己的立场。在王畿的学说可以看到浓郁的“以儒为主”思想，与王阳明相似，王畿将儒家视为心体之“全”，佛老视为心体之“偏”，因此，王畿才能够将佛老的学说吸收、转化，并且引用在自己的论说，如“良知”以及“四无说”。王畿的“良知”说主要强调良知“虚寂”的一面，与佛老的概念融合并且达成和证明“归儒”的想法。而在“四无说”中，王畿则是通过对“无”的诠释，解释良知“纯粹”的状态，并且从中吸收了佛老对“无”的说法。虽然王畿继承大部分王阳明的思想，王畿的良知与王阳明的良知的不同之处就在前者注重良知的“虚寂”而后者注重良知与“天理”。王畿的四无说的核心思想则与王阳明的四句教基本上是一致的。“三教合一”思想在思想界具有争议性，在思想界和民间社会都有重要的影响。“三教合一”历史悠久，在明代时期则由王阳明的心学将此思潮推向巅峰。Wang Ji’s title “Alliance of the Three Teachings” is the result of inheriting his teacher, Wang Yangming’s “Three Teachings One Dao” and “Three Teachings go back to Confucianism” thinking. Not only can Wang Ji respond to Zhu Xi’s accusation of heterodoxy, but he is also able to lay out his position on the minute distinctions between the Confucians, the Buddhists and the Daoists. Similar to Wang Yangming, Wang Ji’s position is based on Confucianism, where he sees Confucianism as having fully grasped the nature of the heart-mind. On the other hand, Buddhism and Daoism only possess a partial understanding. Therefore, Wang Ji can take in, convert, and use the teachings of Buddhism and Daoism in his theories, like liangzhi and four wu. Wang Ji’s liangzhi focuses on the “emptiness” of liangzhi while combining the concept from Buddhism and Daoism, and so proving his “go back to Confucianism” view. While in his four wu theory, Wang Ji uses the concept of “nothingness” in Buddhism and Daoism to explain the absolute and pure state of liangzhi. Even though Wang Ji inherited most of Wang Yangming’s thoughts and teachings, there were still places where they differed from each other, like how Wang Ji focused on the emptiness of liangzhi while the latter focused on liangzhi’s heavenly principles. However, the core thought behind Wang Ji’s four wu is very similar to that of his teacher. “Unity of the Three Teachings” is a controversial concept, and its impact can be seen in both the philosophical world and society. This idea has a long history, but it is when Wang Yangming created the “School of the Heart-Mind” did “Unity of the Three Teachings” reach a new height in the Ming Dynasty.